2003
DOI: 10.1002/prot.10620
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction of 13 yeast SCF complexes with a set of yeast E2 enzymes in vitro

Abstract: SCF complexes are multi-subunit ubiquitin ligases that, in concert with the E1 and E2 ubiquitination enzymes, catalyze the ubiquination of specific target proteins. Only three yeast SCFs have been reconstituted and characterized to date; each of these ubiquitinates its target protein with the E2 Cdc34. We have reconstituted and purified 1 known and 12 novel yeast SCF complexes, and explored the ability of these complexes to function with 5 different purified E2 enzymes; Ubc1, Cdc34, Ubc4, Ubc8 and Ubc11. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 47 publications
3
71
0
Order By: Relevance
“…It has previously been shown that recombinant Dia2 can assemble with SCF components (Kus et al, 2004) and that overexpressed Dia2 assembles with Skp1 and Cdc53 in yeast cells (Ho et al, 2002). We also observed Dia2 assembly with SCF components using an HA 3 -tagged Dia2 baculovirus for expression in insect cells.…”
Section: Dia2 Assembles With Scf Components and Is Required For Normamentioning
confidence: 56%
“…It has previously been shown that recombinant Dia2 can assemble with SCF components (Kus et al, 2004) and that overexpressed Dia2 assembles with Skp1 and Cdc53 in yeast cells (Ho et al, 2002). We also observed Dia2 assembly with SCF components using an HA 3 -tagged Dia2 baculovirus for expression in insect cells.…”
Section: Dia2 Assembles With Scf Components and Is Required For Normamentioning
confidence: 56%
“…What might be the role of Mfb1 and Mdm30 in mediating turnover of Fzo1 and other mitochondrial target proteins? Mdm30 has been shown to interact with Skp1 and Cdc53 in the yeast two-hybrid system (Uetz et al, 2000), recombinant Mdm30 assembles with Skp1, Cdc53, and Rbx1 into an SCF complex in vitro (Kus et al, 2004), and Mfb1 has been found in a complex with Skp1 in large-scale identification of yeast protein complexes by mass spectrometry (Ho et al, 2002) and in coimmunoprecipitation experiments (Kondo-Okamoto et al, 2006). However, Mfb1-Skp1 complexes apparently do not contain Cdc53 (Kondo-Okamoto et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids containing the constructs for Histagged Ubc4 and Ubc11 were kindly provided by Aled Edwards. 22 Plasmid pC105 was constructed by amplifying wild-type CHF2 with added PstI and XhoI sites for insertion into pRS425GAL1. Plasmid pC110 was generated by amplifying the yeast MMS2 gene from a yeast cDNA library with NdeI and XhoI sites for insertion into plasmid pSGA04, 50 which provides an N-terminal His tag.…”
Section: Methodsmentioning
confidence: 99%
“…The enzymes were purified as described 22 with minor modifications. Cell pellets were resuspended in 20 mM HEPES, pH 8.0, 500 mM NaCl, 10% glycerol, 10 μM ZnCl 2 , 5 mM imidazole, 0.5 mM Tris (2-carboxyethyl) phosphine hydrochloride, and protease inhibitor tablets (Roche), and then lysed by sonication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation